Micronucleus and H2AX phosphorylation assessment of silica-coated iron oxide nanoparticles in human neuronal cells - Sánchez-Flores, Maria (2016)
As clinically approved metal oxide nanoparticles, iron oxide nanoparticles (ION) hold immense potential in a vast variety of applications in various fields of biomedicine and biotechnology. With the increase in ION usage, particularly in diagnostics and therapeutics, concerns regarding their interactions with cellular components and possible deleterious effects are also growing.